Curcumin Prevents Acute Neuroinflammation and Long-Term Memory Impairment Induced by Systemic Lipopolysaccharide in Mice - Sorrenti, Vincenzo; Contarini, Gabriella; Sut, Stefania; Dall’Acqua, Stefano; Confortin, Francesca; Pagetta, Andrea; Giusti, Pietro; Zusso, Morena (Frontiers in Pharmacology, 2018)
Systemic lipopolysaccharide (LPS) induces an acute inflammatory response in the central nervous system (CNS) (“neuroinflammation”) characterized by altered functions of microglial cells, the major resident immune cells of the CNS, and increased inflammatory profile that can result in long-term neuronal cell damage and severe behavioral and cognitive consequences. Curcumin, a natural compound, exerts CNS anti-inflammatory and neuroprotective functions mainly after chronic treatment. However, its effect after acute treatment has not been well investigated. In the present study, we provide evidence that 50 mg/kg of curcumin, orally administered for two consecutive days before a single intraperitoneal injection of a high dose of LPS (5 mg/kg) in young adult mice, prevents the CNS immune response. Curcumin, able to enter brain tissue in biologically relevant concentrations, reduced acute and transient microglia activation, pro-inflammatory mediator production and the behavioral symptoms of sickness. In addition, short-term treatment with curcumin, administered at the time of LPS challenge, anticipated the recovery from memory impairments observed one month after the inflammatory stimulus, when mice had completely recovered from the acute neuroinflammation. Together, these results suggest that the preventive effect of curcumin in inhibiting the acute effects of neuroinflammation could be of value in reducing the long-term consequences of brain inflammation, including cognitive deficits such as memory dysfunction.